Sub Bandage Pressure Measurement on a Compressible Limb for Treatment of Leg Ulcer (Journal of Fiber Bioengineering and Informatics, 2016)
Objective: The sub bandage pressure results from a complex interaction between the bandage types,applied tension, number of layers and surface hardness. In this paper, three parameters i.e. hardnessof the limb, stretch (%) and number of bandage layers are changed at three levels and their individualand interactive effect on the sub bandage pressure for different types of high compression bandages isstudied. Method: The study has been conducted on two types of high compression bandages (wovenand knitted) using the Box-Behnken Design. The data obtained for sub bandage pressure of bandagesamples on three plastic tubes with layer of foam of varying hardness is used to carry out responsesurface regression analysis and analysis of variance to find the contribution of each parameter on the subbandage pressure for high compression bandages. Results: The effect of hardness is significant specificallyin the case of woven bandages with some interactive effects with stretch (%) in knitted bandages. Thesub bandage pressure increases with the increase in stretch% for all the samples but larger pressuredifferences were observed for increase in stretch % for limbs with higher hardness. The sub bandagepressure also increases with the number of bandage layers but a linear relationship was not observedbetween sub bandage pressure and the number of layers at low stretch %. The regression equations forvarious responses agree well with the experimental data as indicated by higher values of coefficient ofdetermination. Conclusion: The number of layers and the stretch % contribute substantially towardsthe sub bandage pressure for both woven and knitted bandages. The contribution of hardness of thelimb is found to be insignificant for knitted bandage sample which has the tightest structure and highinitial modulus. The regression equations generated for various responses can be used to predict the subbandage pressure of bandages during application of high stretch bandages.
Keywords: Sub Bandage Pressure; Hardness of Limb; Stretch%; Number of Layers; Regression Analysis